Before the Wright brothers - Berliner, Don. (Minneapolis : Lerner Publications Co., 1990)
Describes the ideas and experiments that lead to the first powered flight by the 1903 "Wright Flyer.".
Includes bibliographical references (p. 69) and index.
Booklist.
School Library Journal.
Wilson's Children.
6.8
6.8
Keywords: Airplanes -- History -- Juvenile literature; Flight -- History -- Juvenile literature; Airplanes -- History; Flight -- History; Airplanes -- History; Flight -- History